2016
DOI: 10.4236/aim.2016.614102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Mycotoxigenic Fungi and Mycotoxins Contaminating Soya Bean Seeds and Processed Soya Bean from Nigerian Markets

Abstract: Concern for food safety has continued to grow worldwide including the issue of mycotoxin contamination of food products from farm to fork. In this regard, soya bean seeds and processed soya bean powder bought from some Nigerian markets were screened for fungal and mycotoxin contamination. Fungal identification was done by both conventional and molecular methods after samples were cultured on potato dextrose agar (PDA), ohio agricultural experimental station agar (OAESA), malt extract agar (MEA) and czapek yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In an LC coupled to tandem MS (MS/MS) method (LC-MS/MS), this C18 reverse-phase SPE column was only used by Chilaka et al [70] to determine FBs, DON and 15-AcDON, ZEN and its metabolites, and HT-2 in maize. Relatively to SAX columns, they were merely employed to purify FBs and further detect them with HPLC-FLD, in soya bean seeds and processed soya bean powder [77] and in maize [73,94]. Plus, for example, grade polypropylene depth hydrophilic-lipophilic balance (GPD HLB) SPE column was applied in UHPLC-MS/MS to determine DON and its derivatives in feed after the extraction with MeCN 50% [93].…”
Section: Mycotoxin Determination Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an LC coupled to tandem MS (MS/MS) method (LC-MS/MS), this C18 reverse-phase SPE column was only used by Chilaka et al [70] to determine FBs, DON and 15-AcDON, ZEN and its metabolites, and HT-2 in maize. Relatively to SAX columns, they were merely employed to purify FBs and further detect them with HPLC-FLD, in soya bean seeds and processed soya bean powder [77] and in maize [73,94]. Plus, for example, grade polypropylene depth hydrophilic-lipophilic balance (GPD HLB) SPE column was applied in UHPLC-MS/MS to determine DON and its derivatives in feed after the extraction with MeCN 50% [93].…”
Section: Mycotoxin Determination Methodsmentioning
confidence: 99%
“…In wheat, co-occurrence between ZEN and DON was found by Calori-Domingues et al [76], in several samples. Already in soybeans and derived by-products, Egbuta et al [77] showed that there was simultaneous occurrence of AFs and FB 1 . Regarding animal feed, Hu et al [78] concluded that combinations of two mycotoxins were more frequent than three but highlighted the presence of AFB 1 , OTA, and ZEN.…”
Section: Mycotoxin Occurrencementioning
confidence: 99%
“…More than 300 mycotoxins have been described, although aflatoxins, trichothecenes, zearalenone (ZEN), fumonisins, ochratoxin A (OTA), and patulin are considered as the most important due to their high toxicity and frequent occurrence in food products [6]. These mycotoxins often contaminate the raw products used to prepare functional beverages including cereals [7,8], legumes [9][10][11][12][13], nuts [11,12,14], fruits [15][16][17], and herbs [18][19][20], among others. This contamination is related to the occurrence of mycotoxin-producing fungi in raw products, which, under permissive conditions, are able to synthetize these compounds at variable levels.…”
Section: Introductionmentioning
confidence: 99%
“…The result revealed the frequency of ZEN (81%), 15-acetyldeoxynivalenol (15-AcDON) (31%), FBs (28%), and HT-2 toxin (HT-2) (25%) in the samples analysed. AF, FB1, and OTA have also been detected in processed soybean powder samples from Nigeria at incidence rates of 45, 100, and 40%, respectively [111]. On the other hand, the susceptibility of groundnut/peanut to fungi and their metabolites has been reported in several countries in SSA [74,77].…”
Section: Oilseed-and Fruit-based Productsmentioning
confidence: 99%